Influence of air flow, temperature and agitation speed in the batch acetification process to obtain orange vinegar (Citrus sinensis var.W. Navel) - Ferreyra, María (2012)
This paper describes the influence of process variables to produce orange vinegar. Orange juice was fermented with Saccharomyces cerevisiae until reach 14% v/v. The biooxidation was carried out with Acetobacter sp., in submerge culture using a laboratory scale fermentor. In order to avoid the inhibitory effect of ethanol on acetic acid bacteria, the orange wine was diluted to 6% v/v with a mineral solution. It was performed a factorial design 2k to study the influence of variables. It was studied air flow rate/agitation at levels of 0.3-0.6 vvm and 200-400 rpm and the effect of air flow rate/temperature at 0.4-0.6 vvm and 25-30°C, respectively. Duplicate treatments were carried out and the results were evaluated in terms of productivity and fermentation yield. Statistical design (p-value<0.05) was analyzed using Statgraphics Centurion XV Corporate software. Treatments performed at 200 rpm and different air flow levels, did not show significant differences on acetification rate. At higher agitation speed and air flow rates, the productivity was high. The best yields were obtained at lower air flows levels and higher agitation speed. Temperature did not present statistically differences on studied variables. The best yield was obtained at 400 rpm and 0.3 vvm at 25°C. It can be concluded that agitation speed plays an important role for a better acetification rate however higher air flow rates causes less yields.